STUDY OF NOISE ON PASSENGER CAR SPEED - Syaiful, Syaiful; Irbah, Almas Fathin (ASTONJADRO, 2021)
Bogor Regency has an economic growth rate including the highest among cities and other districts around the Jakarta Capital Region. Regarding the condition of the vehicle population in Bogor district, the number of motorized vehicles in 2017 and 2018 experienced a growth of between 2% and 12%. In contrast to the growth rate of vehicles, the road growth rate is only 0.1% per year. Nurul Hidayah Mosque is located on Jalan Salabenda, the object of the author's research to find out how much influence the sound of motorized vehicles has on worship activities around the Nurul Hidayah mosque. In public transport car speed, motorcycle speed, and private car speed do not have a significant effect on the noise pollution produced. The noise level around the Nurul Hidayah Mosque, Jalan Salabenda Raya, Bogor Regency which has been measured the smallest is 56.4 dBA. This value exceeds the noise threshold of the Noise Level Standard Value for the Ministerial Decree, which is 55 dBA. So that it requires attention and cooperation from the government and the community to overcome the noise in the worship area. The calculation and analysis obtained is on the equation with the largest R Square value on the fourth day of the study, the third point (Sound Level Meter 3), with a contribution of 22.67%. Like the equation on the side, y = 73.251 + 0.004x1-0.311x2-0.003x3. The meaning of this equation is that if there is no decrease in the speed of motorbikes, private cars and public transport cars, the noise pollution level in SLM3 is 73,251 dBA. If there is an increase in the speed of public transport cars by 0.004, the decrease of motorbikes by 0.311, and an increase in the speed of private cars by 0.003, the noise pollution level will decrease by 0.31 dBA at SLM3.